Legal Awareness of The Public Towards the Prohibition of Giving Money to Beggar (Study in Grendeng Village, North Purwokerto District, Banyumas) - Nitiyoga, Dyaksa; Musyahadah Rahmah, Alef; Alawiya, Nayla (LPPM Universitas Harapan Bangsa, 2025)
This research aims to determine the level of public legal awareness of the prohibition on giving money to beggars and the influence of discipline, motivation, and income factors on public legal awareness of the prohibition on giving money to beggars. This study uses a quantitative research method with a sociological legal approach and descriptive research specifications. The research sample was taken using simple random sampling. The types of data sources include primary and secondary data obtained using questionnaires, documentaries, and literature. The data processing method uses coding, editing, and tabulation techniques, then presented in the form of narrative text and data tables. Data analysis with frequency distribution, cross tables, content analysis, and comparative analysis. The results of the study indicate that the level of public legal awareness of the prohibition on giving money to beggars in Grendeng Village, North Purwokerto District, Banyumas is high. This can be measured by the following indicators: the high level of public legal knowledge of the prohibition on giving money to beggars; the high level of public legal understanding of the prohibition on giving money to beggars; the number of public attitudes of agreement with the prohibition on giving money to beggars; and the number of community behavioral patterns that are in accordance with the prohibition on giving money to beggars. Discipline factors, motivation factors, and income factors tend to have a positive influence on public legal awareness regarding the prohibition on giving money to beggars, meaning that the higher the discipline factors, motivation factors, and income factors, the higher the public legal awareness regarding the prohibition on giving money to beggars.